2008
DOI: 10.1262/jrd.20060
|View full text |Cite
|
Sign up to set email alerts
|

A 12-month Feeding Study of Reproduction/Development in Rats Fed Meat/Milk Powder Supplemented Diets Derived from the Progeny of Cloned Cattle Produced by Somatic Cell Nuclear Transfer

Abstract: Abstract. The present 12-month feeding study was carried out with rat groups fed a diet supplemented with meat or milk (meat/milk) derived from the progeny of clones produced by somatic cell nuclear transfer (SCNT) technology. It was conducted to obtain data concerning the chronic toxicities of these edible products during the process of development and reproduction in rats fed such products. The rats were subjected to clinical observations for general health condition and examinations such as sensory/reflex f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Similar results were obtained by in a 21 d feeding test with a diet containing milk and meat from cattle clones (F0) (Heyman et al, 2007). A 12 mon oral toxicity study in the rat with meat and milk from the progeny of cattle clones (F1) was done in Japan and as the results, there were no biologically significant differences in composition among clones, their progeny and conventionally bred cattle (Yamaguchi et al, 2008).…”
Section: Food Consumption Risksupporting
confidence: 73%
“…Similar results were obtained by in a 21 d feeding test with a diet containing milk and meat from cattle clones (F0) (Heyman et al, 2007). A 12 mon oral toxicity study in the rat with meat and milk from the progeny of cattle clones (F1) was done in Japan and as the results, there were no biologically significant differences in composition among clones, their progeny and conventionally bred cattle (Yamaguchi et al, 2008).…”
Section: Food Consumption Risksupporting
confidence: 73%
“…Regarding the difference in total bilirubin concentrations between two control groups (vanadic oxidation method and Jendrassik-Grof method), although the reason for the difference is not clear at present, a similar tendency was reported in the rat studies. That is, total bilirubin concentration measured by Jendrassik-Grof method was much higher than that measured by the vanadic acid oxidation method (Sirota et al, 2008;Yamaguchi et al, 2008). In addition to total bilirubin concentrations, all of the FX groups showed significantly higher total cholesterol concentrations than those in the corresponding control groups.…”
Section: Discussionmentioning
confidence: 85%
“…However, considerable evidence has shown that the health [7,8,11,12], reproduction [12,15], meat and milk quality [18], and intelligence [14][15][16] of cloned animals are comparable to those from naturally produced animals. The social behavior of cloned animals has also been shown to be similar to non-cloned animals [28].…”
Section: Discussionmentioning
confidence: 99%
“…The cloned bulls derived from an aged and infertile bull had normal fertility [17]. Also, nutritional evaluation of milk and meat by rat feeding experiments showed that no differences were found between products derived from clones versus controls [18]. Immune status analysis suggests that cloned cattle present a normal representation of leukocyte subsets and functional immunity was not modified in cloned heifers [19].…”
Section: Introductionmentioning
confidence: 99%